Symbiosis without return: Study of the subjects, objects, and heritage values of the mercado modelo of Chiclayo, Lambayeque - Sierralta Escudero, Nuria (2025)
The objective of this research was to uncover the heritage values of the Modelo Market in the city of Chiclayo, Lambayeque, Peru, from the perspective of the symbiosis between the object (the market) and the heritage actors that comprise it. A mixed approach (qualitative-quantitative) was employed to provide a holistic understanding of the phenomenon, analyzing how social actors interact with the market's infrastructure and its surroundings. Finally, based on the results obtained, it is concluded that the market, throughout its extensive existence, has generated a sense of identity and belonging among the population, not only of Chiclayo but of the entire region. In the context of heritage values, it is the use value that, due to its nature and characteristics, determines the practical sense of the place.